Effect of Patient Demographics on Minimally Important Difference of Ankle Osteoarthritis Scale Among End-Stage Ankle Arthritis Patients. (May 2021) - Sutherland, Jason M.; Albanese, Carmela Melina; Wing, Kevin; Zhang, Yixiang Jenny; Younger, Alastair; Veljkovic, Andrea; Penner, Murray
Background: Ankle replacement and ankle arthrodesis are standard treatments for treating end-stage ankle arthritis when conservative treatment fails. Comparing patient-reported outcome scores to the instrument's minimal important difference (MID) helps physicians and researchers infer whether a meaningful change in health from the patient's perspective has occurred following treatment. The objective of this study was to estimate the MID of the Ankle Osteoarthritis Scale among a cohort of operatively treated end-stage ankle arthritis patients undergoing ankle replacement or arthrodesis. Methods: A survey package including the Ankle Osteoarthritis Scale was completed by participants preoperatively and 2 years postoperatively. Distribution and anchor-based approaches to calculating the MID were used to estimate the MID of the Ankle Osteoarthritis Scale and its 2 domains. The distribution-based approaches used were the small and medium effect size methods, while the mean absolute change method and linear regression method were the anchor-based approaches. Bootstrap sampling was used to obtain the variance of MID estimates. The MID was estimated for sex, age, operative, and baseline health subgroups. The cohort comprised 283 participants, totaling 298 ankles. Results: The MID did not vary with sex or operative procedure. Age-based differences in MID values may exist for the Ankle Osteoarthritis Scale total score, and MID values were generally smallest among the oldest patients. Patients with the best and worst ankle-related health preoperatively had higher MID values than patients reporting mid-range Ankle Osteoarthritis Scale values preoperatively. Conclusion: The best estimate of the MID of the Ankle Osteoarthritis Scale total score is 5.81. Our findings indicate that the MID of the Ankle Osteoarthritis Scale may not vary by sex or operative subgroups but likely varies by age and preoperative Ankle Osteoarthritis Scale score. Level of Evidence: Level II, prospective comparative study.